SOCIAL RESPONSIBILITY OF AGROCOMPLEX ENTERPRISE/COMPANIES IN TIMES OF CRISIS - Živković, Dragan; Vujić, Tamara; Cvijanović, Dušica (Economics of Agriculture, 2021)
The paper points out the maintenance of economic activity and stability of production even in the difficult conditions of the global crisis as a consequence of the pandemic. Especially in the conditions of a long-lasting crisis, caused by a pandemic of the virus, the business or social responsibility of companies in the agro-industrial sector of the economy is observed. The aim of this paper is that, in the conditions of business crisis, social responsibility represents the optimal attendance of companies from the observed activity, and thus to contribute to the sustainability of economic development. The main goal of the paper is that, even in the conditions of the great business crisis – caused by covid 19 virus, in all economic branches and especially food producers, the socially responsible behavior of companies in the agricultural complex does not disappear. The subject of the research is the business of the company "Agroprogres" i.e. the way and model of applying the concept of social responsibility in the conditions of a great and general business crisis and the adaptability of the company from the agro complex to new circumstances. Pursuant to the subject of the research the target group of employees was selected and a survey was conducted from the aspect of the level of social responsibility of the company. Analyzing the business of a particular company, many scientific methods were used to prove the basic hypothesis: the crisis caused by the pandemic did not reduce social responsibility during its duration, i.e. business in difficult conditions.